Private Money for the Public Good: Higher Education Philanthropy in Canada and the United States - Stacy G. Kelly (Canadian Society for Studies in Education, 2009)
With the establishment of higher education institutions in the 17th century in both Canada and the United States, concerns over what should be the level of funding for higher education, and who should primarily be responsible for providing it has been a longstanding public policy debate. The critical pivot point for each country has been the varying roles of the state and the individual in funding higher education. How these roles were defined in each country framed the rise of philanthropy in higher education. This paper will trace the role of philanthropy in the development of higher education in Canada and the United States.